2015
DOI: 10.1017/s0025315415000740
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and host–parasite interrelationship of Mytilus galloprovincialis parasites in Turkish Black Sea coasts

Abstract: This is the first comprehensive research study on the parasites of Mytilus galloprovincialis collected from the Sinop coasts of the Black Sea and their relationships with several environmental and biotic factors. A total of 1740 mussels were collected monthly at three sampling localities representing different ecosystems in the period between August 2012 and July 2013 and examined for parasites. Identified parasites were Nematopsis legeri, Peniculistoma mytili, Urastoma cyprinae, Parvatrema duboisi and Polydor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Among the parasites infecting two types of hosts (mollusks and crustaceans) (PRYTHERCH, 1938(PRYTHERCH, , 1940, we highlight the genus Nematopsis Schneider, 1892 (Apicomplexa: Porosporidae). This is a cosmopolitan parasitic genus of apicomplexans with around 40 nominal species that have been reported in different geographic areas (ABDEL-BAKI et al, 2012;AZEVEDO & MATOS, 1999;AZEVEDO & PADOVAN, 2004;BOWER et al, 1994;OZER & GUNEYDAG, 2015;SPRAGUE, 1970;THÉODORIDÈS, 1962;TUNTIWARANURUK et al, 2004). Their vegetative and reproductive phase takes place in crustaceans (schizogonic phase), while the sporogonic phases take place in bivalves (PRYTHERCH, 1938(PRYTHERCH, , 1940.…”
Section: Introductionmentioning
confidence: 99%
“…Among the parasites infecting two types of hosts (mollusks and crustaceans) (PRYTHERCH, 1938(PRYTHERCH, , 1940, we highlight the genus Nematopsis Schneider, 1892 (Apicomplexa: Porosporidae). This is a cosmopolitan parasitic genus of apicomplexans with around 40 nominal species that have been reported in different geographic areas (ABDEL-BAKI et al, 2012;AZEVEDO & MATOS, 1999;AZEVEDO & PADOVAN, 2004;BOWER et al, 1994;OZER & GUNEYDAG, 2015;SPRAGUE, 1970;THÉODORIDÈS, 1962;TUNTIWARANURUK et al, 2004). Their vegetative and reproductive phase takes place in crustaceans (schizogonic phase), while the sporogonic phases take place in bivalves (PRYTHERCH, 1938(PRYTHERCH, , 1940.…”
Section: Introductionmentioning
confidence: 99%
“…in the horse-bearded mussel Modiolus barbatus Linnaeus, 1758 in Mali Ston (Adriatic Sea, Croatia). Urastoma cyprinae turbellarians were found in low prevalence in our study, as was similarly observed in M. galloprovincialis from Baja California, north-west Mexico (Caceres-Martinez et al ., 1998) and from the Black Sea coast at Sinop, Turkey (Özer & Güneydağ, 2015). Moreover, low prevalence of U. cyprinae was found in the mangrove oyster Crassostrea rhizophorae (Guilding, 1828) in the estuary of the Graciosa River in Taperoá, Bahia State, north-east Brazil (Cova et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The most severe mussel diseases are caused by viruses, bacteria and protistans, which can be responsible for mortality outbreaks, thus posing a substantial commercial impact (Tuntiwaranuruk et al ., 2008; Ceuta & Boehs, 2012; Mladineo et al ., 2012). To a lesser extent, other diseases are caused by ciliates, turbellarians (Cova et al ., 2015), trematodes (Özer & Güneydağ, 2015) and fungi (Santos et al ., 2017). The spread of fungal strains may be facilitated by a combination of environmental conditions, such as wind or human-conveyed propagules (Sallenave-Namont et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Shimura et al [ 27 ] settled the name of this parasite as P. duboisi . Now the geographical distribution of P. duboisi has been extended from France [ 21 – 24 ] to Japan [ 15 , 25 – 27 ], Korea [ 2 , 8 , 10 , 12 , 13 ], Ukraine [ 28 ], and Turkey [ 29 ].…”
mentioning
confidence: 99%
“…The second intermediate host of P. duboisi had been repeatedly confirmed to be marine bivalves or clams, including M. galloprovincialis [ 24 , 28 , 29 ], Brachydontes minimus [ 24 ], Venus gallina [ 24 ], and the Manila clam R. philippinarum [ 2 , 8 , 10 , 12 , 13 , 15 , 25 – 27 ]. However, its first intermediate host and the developmental (larval) stages of parasites were only recently discovered by Yanagida et al [ 15 ].…”
mentioning
confidence: 99%